Myrmecobius fasciatus (Dasyuromorphia: Myrmecobiidae) - Cooper, Christine (2011)
Myrmecobius fasciatus Waterhouse, 1836, is a small to medium-sized dasyuromorph marsupial known as the numbat. M. fasciatus is unusual among marsupials in that it is diurnal and feeds exclusively on termites, and it has a number of characteristic adaptations associated with this specialized niche. M. fasciatus has at least 8 postcanine teeth in the lower jaw; the dentition is variable between individuals and even between the 2 sides of the jaw of the same individual. Although widespread throughout southern Australia at the time of European settlement, M. fasciatus is currently restricted to 2 naturally occurring populations in the southwestern portion of Western Australia, and some additional populations within its historic range resulting from successful reintroductions. It is currently listed as ‘‘Endangered.’’